Creative Cities and Regional Development: the Case of Makhanda and the Creative City Project - Campbell, Guy John (Rhodes University, Faculty of Commerce, Department of Economics and Economic History, 2021)
The 'Creative City' is a popular term describing a method of regional/urban development through the development of creative and cultural industries (CCIs). Research into this topic has mostly focused on large cities in developed nations. Research into its applicability to small, underdeveloped regions located in developing nations has been severely limited. This research drew on the creative city theory of Richard Florida (2002) and other relevant literature in the realm of creative and cultural economics. The extent to which the 'Creative City' Project of Makhanda, located in the Eastern Cape Province of South Africa, was successful in meeting its stated goals was assessed. The institutional frameworks and operational context of the project were investigated. A mixed-methods approach was applied. This included qualitative research techniques, drawing from multiple international and national case studies and literature. It also involved interviews with key stakeholders involved with the project. A quantitative survey assessed the extent to which the project has been successful in its goal to market Makhanda as the "Creative City" and whether it could become "South Africa's Creative and Cultural Capital" . There is no reliable standard blueprint for how to develop a creative city. However, factors for success can be found in the development of new and growing creative spaces for the centralisation of creative and cultural activity; in associated employment opportunities and industry experience made available; and in strong partnerships forged between the project, local government and a range of key stakeholders. The Makhanda project faced significant challenges "“ namely, scarce financial support, small local consumer markets, an insufficiently recognised brand, limited support from local business and no vertical alignment with the national policy agenda. Despite the challenges several advantages were identified, including; a generous endowment in hard and soft infrastructures, a socially diverse and open environment, and a project rooted in the community interest. The project exhibits the potential to develop a thriving arts and culture sector in Makhanda. But it will be critical for the project to become self-sufficient and remain, and further embed itself, in the interests of the broad community for whom the project ultimately aims to benefit.
Keywords: Creative City; Regional development; Cultural economics; Creative economy; Cultural industry; Creative industries